Interaction in Educational Domains - Tirri, Kirsi; Kuusisto, Elina; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
In this volume, we take a holistic approach to education, viewing human beings as lifelong learners who need interaction in all educational domains - cognitive, affective, psychomotor - to actualize their full potential. The chapters are based on presentations given at the 2012 conference of the Finnish Educational Research Association (FERA), whose theme was Interaction in Educational Research. Prof. David Clarke, from the University of Melbourne in Australia and the conference's keynote speaker, opens our symposium with a discussion of international comparative research in educational interaction by constructing and concealing differences. The chapters that follow, arranged in three parts, deal with interaction in cognitive, affective, and psychomotor domains. In Part I, theoretical and philosophical approaches to interaction are examined through ontological, epistemological, and semiotic perspectives. Part II presents a series of empirical studies on educational interaction. Together, these show regional differences in cognitive and psychomotor learning outcomes, the importance of academic emotions in learning, cultural aspects in understanding the visual arts, and interactive learning for gifted science students. Part III introduces three programs that promote educational interaction: one enhances teacher education with interdisciplinary integration; another explores the benefits of Finnish-Russian cooperation; and a third uses musical concerts as an interactive tool for special education. All of the chapters contribute to the current research and discussion on learning and interaction. In this field inquiries need to be carried out in different learning domains and in various cultural contexts. In particular, cross-cultural comparisons are useful in validating the findings of empirical studies and testing the culture-dependent and culture-invariant dimensions of educational interaction.
Keywords: Education; Education